2019
DOI: 10.1186/s12984-019-0601-1
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of using 3D virtual reality based training in persons with Parkinson’s disease: a parallel study

Abstract: Background Parkinson’s disease (PD) is a slowly progressive neurodegenerative disease. There are mixed reports on success of physiotherapy in patients with PD. Our objective was to investigate the functional improvements, motivation aspects and clinical effectiveness when using immersive 3D virtual reality versus non-immersive 2D exergaming. Methods We designed a randomized parallel study with 97 patients, but only 20 eligible partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
95
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(109 citation statements)
references
References 38 publications
6
95
0
8
Order By: Relevance
“…The results from their study demonstrated that the use of immersive 3D technology might increase interest and enjoyment in therapy compared to intervention with LMC, and produce faster and more efficient functional performance and reduced resting tremors as assessed by BBT, UPDRS III, and LMC. Our results are in line with Cikajlo and Potisk [57]. Fernández-González [3] conducted a randomized controlled trial using LMC and serious games compared to conventional UL rehabilitation in PD patients.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The results from their study demonstrated that the use of immersive 3D technology might increase interest and enjoyment in therapy compared to intervention with LMC, and produce faster and more efficient functional performance and reduced resting tremors as assessed by BBT, UPDRS III, and LMC. Our results are in line with Cikajlo and Potisk [57]. Fernández-González [3] conducted a randomized controlled trial using LMC and serious games compared to conventional UL rehabilitation in PD patients.…”
Section: Discussionsupporting
confidence: 88%
“…Few studies have been conducted concerning the use of technology to improve dexterity and coordination in UL rehabilitation [3,[55][56][57].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, virtual reality (VR) is technology used to simulate an environment that users experience as being comparable to the real world [11]. Previous studies showed that VR training promotes recovery of upper limb functions in patients with stroke or Parkinson's disease [12][13][14]. Therefore, VR training may be used in acquiring bp-prosthetic control.…”
Section: Introductionmentioning
confidence: 99%